Detection and characterization of fibropapilloma associated herpesvirus of marine turtles in Rio Grande do Sul, Brazil - Carla R. Rodenbusch; Laura L. Almeida; Fernanda S. Marks; Michelli W. Ataíde; Marcelo M. Alievi; Maurício Tavares; Rosecler Alves Pereira; Cláudio W. Canal (Pesquisa Veterinária Brasileira, 2012)
Fibropapillomatosis (FP) is a benign tumoral disease that affects sea turtles, hampering movement, sight and feeding, ultimately leading to death. In Brazil, the disease was described for the first time in 1986. Research suggests the involvement of a herpesvirus in association with environmental and genetic factors as causal agents of FP. The objective of the present study was to detect and characterize this herpesvirus in sea turtles living in the coast of state Rio Grande do Sul (RS), Brazil. From October 2008 to July 2010, 14 turtles were observed between the beaches of Torres and Tavares, of which 11 were green turtles (Chelonia mydas) and 3 were loggerhead turtles (Caretta caretta). All turtles were young and mean curved carapace length was 37.71±7.82cm, and varied from 31 to 55cm. Only one green turtle presented a 1cm, papillary, pigmented fibropapilloma. Skin and fibropapilloma samples were analyzed by conventional and real time PCR assays to detect and quantify herpesvirus. All skin samples were negative, though the fibropapilloma specimen was positive in both tests. Viral load was 9,917.04 copies of viral genome per milligram of tissue. The DNA fragment amplified from the fibropapilloma sample was sequenced and allocated in the Atlantic phylogeographic group. This study reports the first molecular characterization of herpesvirus associated with fibropapilloma in turtles from the coast of RS.